Literature Review: The Role of Magnetic Nanoparticles in Several Fields of Life - Lailatul Machfudhoh (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2023)
There has been a lot of research on nanoparticles which have been developed for application in everyday life. One type of nanomaterial that has been discussed is magnetic nanoparticles. Some areas of life that apply magnetic nanoparticles for example are in the medical and biological fields, the field of sensors, the field of water and waste treatment, and others. The results of this literature review discuss the role of magnetic nanoparticles in everyday life.